Prevalence and Use of Dietary Supplements Among Pharmacy Students in Saudi Arabia - Samreen S; Siddiqui NA; Wajid S; Mothana RA; Almarfadi OM (Dove Medical Press, 2020)
Sana Samreen,1 Nasir A Siddiqui,2 Syed Wajid,3 Ramzi A Mothana,2 Omer M Almarfadi2 1Department of Pharmacy, College of Pharmacy, Aurobindo College of Pharmaceutical Sciences, Warangal, India; 2Department of Pharmacognosy, College of Pharmacy, King Saud University, Riyadh, Saudi Arabia; 3Department of Clinical Pharmacy, College of Pharmacy, King Saud University, Riyadh, Saudi ArabiaCorrespondence: Syed Wajid Tel +966-11-4677256Fax +966-11-4677245Email wali@ksu.edu.saPurpose: Dietary supplements (DSs) are popular in many countries, and their use among individuals is increasing worldwide. Therefore, this study aimed to assess the prevalence and use of DSs among pharmacy students in King Saud University College of Pharmacy, Riyadh, Saudi Arabia.Methods: This study used a cross-sectional design targeting male senior pharmacy students in their fourth and fifth years of Bachelor and Doctor of Pharmacy courses. The data were collected between August and October 2019 using paper-based questionnaires.Results: A total of 46.8% of the students used DSs. Of all students surveyed, 19% used branded supplements whereas 9.7% used generic or local supplements and 12.3% used both generic and branded supplements. Furthermore, 8.2% students suffered from side effects, including 5.6% who suffered from nausea, vomiting, and diarrhea and 2.6% who suffered from headache, confusion, and disorientation. Approximately 24.6% of students used fiber DSs whereas 19% and 16.4% used DSs for protein and glucosamine/omega 3 fatty acids, respectively.Conclusion: The study findings indicated that the prevalence of DS use is increasing. However, approximately half of the respondents encourage the use of DSs only with a doctor’s recommendation. Educating about the safe use of DSs is warranted.Keywords: dietary supplements, performance boosters, pharmacy students, minerals, vitamins, Saudi university